Can self-esteem mediate the association between social support and different levelsof physical activity in adolescents? - Lopes, Vítor P. (2022)
The aim was to analyze the mediation role of self-esteem in the interaction between social support from the best friend, friends, and parents, and physical activity (PA). Participants were N=444 adolescents of both genders (male= 205), aged between 12-18 years (M= 16.02; SD= 1.57). Structural equation modeling, serial mediation and multigroup analysis were used to test the proposed hypothesis. Self-reported instruments were used to collect both PA social support and self-esteem. Self-esteem partially mediates the interaction between different social supports and vigorous PA, independently of adolescent sex. Interestingly, self-esteem fully mediated the interaction between parents’ social support and vigorous PA in female adolescents. In contrast, self-esteem revealed no mediation in the interaction between social support and light and moderate PA. In conclusion, self-esteem mediates the relationship between social support and vigorous PA, the strength of mediation is higher in girls than in boys, in both genders, the mediation is higher when the social support has come from parents.